Mechanism of Rh(III) Catalysis in Oxidation of Glutamic Acid by Alkaline Solution of Hexacyanoferrate(III) - Kumar Singh, Birendra; Singh, R.P. (Asian Journal of Chemistry, 2010)
Kinetics of Rh(III) catalysed hexacyanoferrate(III) oxidation of glutamic acid in alkaline medium have been studied. The reaction showed zero-order dependence on hexacyanoferrate(III) and OH– ion and first order kinetics with respect to both glutamic acid and Rh(III). Insignificant effect of variation of ionic strength of the medium was observed. A suitable mechanism consistent with kinetic data is proposed.